Discrete complexed ligand and catalytic nickel peaks in the differential pulse polarography and cathodic stripping voltammetry of Mordant Red 74 - Fogg, Arnold G.; Ismail, Razali; Ahmad, Rahmalan; Willia, Sian L.; Zanonia, M. Valnice (Elsevier, 1997)
Cathodic stripping voltammograms of Mordant Red 74 obtained in the presence of nickel ion exhibit both a discrete complexed ligand peak and a catalytic nickel peak. The complexed ligand peak is discrete from the free ligand peak and the catalytic nickel peak is discrete from the diffusion-controlled free nickel peak. It would be possible, using a slight excess of Mordant Red 74, to determine nickel using the complexed ligand peak, and it is possible to determine Mordant Red 74 in the presence of a relatively large excess of nickel using the catalytic nickel peak. This latter method has much greater sensitivity than can be obtained with the direct use of the Mordant Red 74 peak in the absence of nickel. The attainment of improved detection limits for the determination of Mordant Red 74, using the catalytic nickel peak, however, is restricted by the need, at very low concentrations of Mordant Red 74, to reduce the concentration of nickel used in order to resolve the catalytic and free nickel peaks: the decrease in nickel concentration near the electrode surface reduces the catalytic activity.